Monte Carlo Simulations in the Search for New Physics in the Lepton, b-jet and Missing Energy Signature at the CMS Experiment (2025)
Several studies have shown the possibility of finding new physics in final states containing lepton, b-jet and missing energy at the CMS experiment in LHC proton-proton collisions. In this sense, a experimental search is relevant in front of the possible connections with observed anomalies in the quark b sector. In this thesis, we present the Monte Carlo signal simulation of three different models varying the mass of the mediator.